Manajemen Sumber Daya Manusia pada Era Digitalisasi - Ahmad Gunawan; Amelia Sri Rizki; Tabina Farrah Anindya; Assyfa Putri Amalia; Winda Fara Setiani (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
Digitalization in human resource management helps companies modernize HR functions and provides competitive advantages.At the same time, changes in work styles and demand for HR skills are also required.The aim of this research is to introduce the phenomenon of digitalization into the literature, investigate its current main benefits and risks, and analyze the impact of digitalization on the competencies and roles of human resources professionals.This qualitative study includes secondary data describing current levels of digital skills, based on more than 7 responses.respondents from six EU member states (Germany, Finland, UK, Portugal, Sweden and Slovakia.Contains analysis).Primary data analysis of HR social media skills collected in five European countries participating in the SHARPEN project is also presented here.This article also discusses recent trends in HR specialist skills.The results obtained indicate that HR professionals tend to be reluctant to adopt these technologies.The results of this survey highlight the importance of digitalization and the increasing need for digital skills for human resources in recent years.